Pelaksanaan Pembelajaran Coding SDN Pandean Lamper 05 - Aprilia Maziyah, Fifa; Wakhyudin, Husni (UNIVERSITAS SERAMBI MEKKAH, 2025)
This study aims to evaluate the implementation of coding learning at SDN Pandean Lamper 05 using an innovative game-based approach through the “code.org” platform. The research team provided a course specifically designed for 3rd-grade elementary students with an appropriate difficulty level. The course includes various interactive learning stages in the form of games such as puzzles, robots, squirrels, and Angry Birds, designed to introduce basic coding concepts in an enjoyable way. The course type used is Course A, which is part of the introductory material available on the “code.org” platform. The results indicate that the game-based approach successfully increases students’ interest and understanding of basic programming concepts. Through this method, students were more motivated to complete the given challenges and were able to think logically and creatively in solving problems. This study recommends the broader implementation of game-based coding learning to enhance technology literacy among elementary school students.